2022
DOI: 10.1109/access.2022.3151792
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Outdated CSI on the Secure Communication in Untrusted In-Band Full-Duplex Relay Networks

Abstract: To provide reliable connectivity in recent and future wireless communication systems, it is necessary to deploy several relay nodes. Further, a full-duplex (FD) technique has been in the spotlight since it can significantly improve spectral efficiency, and thus recent studies in relaying networks have considered FD relays. In relaying networks, confidentiality between the source and destination nodes from the relay node should be carefully kept, especially, when the relay node is not fully trusted, so-called u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Their results showed that the RIS-FD model improves the spectrum efficiency and that it also significantly weakens eavesdroppers' capability to detect legitimate signals by directing multiple superimposed signals toward the eavesdropper. The authors in [84] proposed a secure relaying protocol to protect against untrusted FD relay nodes based on PLS. In doing so, they assumed that Bob generates AN signals to prevent the untrusted relay from decrypting Alice's data.…”
Section: Min Sopmentioning
confidence: 99%
“…Their results showed that the RIS-FD model improves the spectrum efficiency and that it also significantly weakens eavesdroppers' capability to detect legitimate signals by directing multiple superimposed signals toward the eavesdropper. The authors in [84] proposed a secure relaying protocol to protect against untrusted FD relay nodes based on PLS. In doing so, they assumed that Bob generates AN signals to prevent the untrusted relay from decrypting Alice's data.…”
Section: Min Sopmentioning
confidence: 99%
“…where I r ½i can be modeled as a Gaussian random variable with mean zero and variance l 2 r P [18,22]. l r corresponds to the self-interference cancellation capability at the relay.…”
Section: System Modelmentioning
confidence: 99%
“…Based on the source jamming scheme, [17] derived the secrecy outage probability for untrusted fullduplex relay networks. The impact of outdated channel state information (CSI) on the ergodic secrecy rate of untrusted full-duplex relay networks was investigated in [18]. The authors of [19] proposed an artificial noise-aided secure transmission scheme to confuse the untrusted full-duplex relay and external eavesdroppers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the integration of PLS and cryptographic techniques with existing upper layers is a promising approach for future secure wireless networks [13]. In this context, the application of PLS to essential technologies, such as device-to-device communication [14,15] and full duplex [16,17], has been studied.…”
Section: Introductionmentioning
confidence: 99%